2016
DOI: 10.1177/0363546516634679
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Incidence and Return-to-Play Time in National Basketball Association Players

Abstract: Although the incidence of publicly reported concussions in the NBA has not changed appreciably over the past 9 seasons, the time missed after a concussion has. While players often returned in the same game in the 2006 season, the combination of implemented policy, national coverage, medical staff awareness, and player education may have contributed to players now missing an average of 4 to 6 games after a concussion. A multitude of factors has resulted in more conservative return-to-play practices for NBA play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 24 publications
3
32
1
Order By: Relevance
“…36 Nasal bone fractures were the most common type of facial fracture sustained by NBA players in our study, which supports previous literature, both at professional and recreational levels. 7,9,10,26,36 Orbital fractures were also commonly sustained by NBA players in our study, which supports previous findings that orbital fractures are more common in basketball than other sports. 13 We found 57 cases of facial fracture over 33 seasons, translating to an incidence of 1.727 facial fractures per NBA season; yet, the actual rate is likely higher due to study limitations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…36 Nasal bone fractures were the most common type of facial fracture sustained by NBA players in our study, which supports previous literature, both at professional and recreational levels. 7,9,10,26,36 Orbital fractures were also commonly sustained by NBA players in our study, which supports previous findings that orbital fractures are more common in basketball than other sports. 13 We found 57 cases of facial fracture over 33 seasons, translating to an incidence of 1.727 facial fractures per NBA season; yet, the actual rate is likely higher due to study limitations.…”
Section: Discussionsupporting
confidence: 91%
“…This statistic is likely underreported, given that in the 1980s/1990s concussions were poorly understood and routinely undocumented, and that the NBA did not enforce a formal, unified concussion policy before the 2011 to 2012 season. 26 The incidence of traumatic head injury in patients who suffer maxillofacial fracture ranges from 5.4% to 86% depending on mechanism of injury. 16 Although a recent study found that NBA player performance was unaffected in the initial five games following concussion, this finding is still notable in the context of the league.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the current evidence that players do not demonstrate a postconcussion decline in performance, it should be emphasized that this conclusion is predicated on proper concussion diagnosis and management. Recently, Padaki et al [40] assessed the epidemiology of concussion in the NBA before and after the institution of the concussion policy. The number of games missed following concussions increased threefold According to Wilcoxon Signed Ranks Test.…”
Section: Concussion Management In the Nbamentioning
confidence: 99%
“…5,48,50,53 In each of these professional leagues, authors have reported that the institution of league-wide, formalized concussion policies resulted in increases in concussion incidence. 26,37,50 However, in one of the relatively few investigations that has studied concussions in NBA players, Padaki et al 45 found that incidence was not statistically different following the institution of the NBACP but that RTP time had increased. In their study, the authors were limited by a relatively small sample size of years included, which they acknowledged.…”
mentioning
confidence: 99%